Small Caribbean (CARICOM) states get involved in management of shared large pelagic species - Singh-Renton, Susan (2003)
Provides a view of the current situation regarding large pelagic fisheries in CARICOM countries. Examines the implications for these fisheries, of recent trends in international management approaches to Atlantic tuna and tuna-like fisheries.